Growth/Differentiation Factor-15 (GDF-15): From Biomarker to Novel Targetable Immune Checkpoint - Wischhusen, Jörg; Melero, Ignacio; Fridman, Wolf Herman (Frontiers in Immunology, 2020)
Growth/differentiation factor-15 (GDF-15), also named macrophage inhibitory cytokine-1, is a divergent member of the transforming growth factor β superfamily. While physiological expression is barely detectable in most somatic tissues in humans, GDF-15 is abundant in placenta. Elsewhere, GDF-15 is often induced under stress conditions, seemingly to maintain cell and tissue homeostasis; however, a moderate increase in GDF-15 blood levels is observed with age. Highly elevated GDF-15 levels are mostly linked to pathological conditions including inflammation, myocardial ischemia, and notably cancer. GDF-15 has thus been widely explored as a biomarker for disease prognosis. Mechanistically, induction of anorexia via the brainstem-restricted GDF-15 receptor GFRAL (glial cell-derived neurotrophic factor [GDNF] family receptor α-like) is well documented. GDF-15 and GFRAL have thus become attractive targets for metabolic intervention. Still, several GDF-15 mediated effects (including its physiological role in pregnancy) are difficult to explain via the described pathway. Hence, there is a clear need to better understand non-metabolic effects of GDF-15. With particular emphasis on its immunomodulatory potential this review discusses the roles of GDF-15 in pregnancy and in pathological conditions including myocardial infarction, autoimmune disease, and specifically cancer. Importantly, the strong predictive value of GDF-15 as biomarker may plausibly be linked to its immune-regulatory function. The described associations and mechanistic data support the hypothesis that GDF-15 acts as immune checkpoint and is thus an emerging target for cancer immunotherapy.